Efektifitas Metode Kooperatif Learning Terhadap Hasil Belajar Pada Pembelajaran Tematik SDI SABILILLAH Kelas V Tahun Ajaran 2023 - Tsalis Nur Zamzami (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to determine the effectiveness of the Cooperative Learning Method in the teaching and learning process of class V Thematic Material at SDI Sabilillah Cukir, in addition, this Cooperative method also has a role in the learning process so that students are able to learn compactly and help each other in the learning process and have a sense of responsibility. This type of research is qualitative Pre Experimental, the subjects of the study were class V students of SDI Sabilillah Cukir, this study was conducted in the even semester in May of the 2023 academic year. This research instrument used an initial test (Pre test) and (Post test) final test. Thus, the N data in class VA SDI Sabilillah Cukir totaling 25 students. The average (Mean) of the Posttest is 64.6 and Posttest 81. So from the analysis above Ho is rejected and H1 is accepted, this shows that there is effectiveness in learning outcomes that are treated using the cooperative learning method.